2014
DOI: 10.1126/science.1256271
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin state dynamics during blood formation

Abstract: Chromatin modifications are crucial for development, yet little is known about their dynamics during differentiation. Hematopoiesis provides a well-defined model to study chromatin state dynamics, however technical limitations impede profiling of homogeneous differentiation intermediates. We developed a high sensitivity indexing-first chromatin immunoprecipitation approach (iChIP) to profile the dynamics of four chromatin modifications across 16 stages of hematopoietic differentiation. We identify 48,415 enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
920
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 731 publications
(961 citation statements)
references
References 30 publications
41
920
0
Order By: Relevance
“…This field has been propelled by remarkable technological advances for efficiently isolating single cells 28, 29, and the reduction of the detection levels of protocols for profiling gene expression 30, 31, histone marks 25, 26, or chromatin accessibility 32, 33 in individual cells. These techniques allow researchers to overcome the limitations of population studies, in which averaging the measurements over a heterogeneous population of cells masks the variability at the epigenetics and transcriptional levels among cells within a culture or tissue 26, 34, 35.…”
Section: Single‐cell Profiling Is Key For Studying Pluripotent Statementioning
confidence: 99%
See 4 more Smart Citations
“…This field has been propelled by remarkable technological advances for efficiently isolating single cells 28, 29, and the reduction of the detection levels of protocols for profiling gene expression 30, 31, histone marks 25, 26, or chromatin accessibility 32, 33 in individual cells. These techniques allow researchers to overcome the limitations of population studies, in which averaging the measurements over a heterogeneous population of cells masks the variability at the epigenetics and transcriptional levels among cells within a culture or tissue 26, 34, 35.…”
Section: Single‐cell Profiling Is Key For Studying Pluripotent Statementioning
confidence: 99%
“…Profiling of the epigenetics landscape of individual cells has shown that lineage‐specific master regulators are associated with single‐cell epigenomic variability across several cell types, suggesting that control of single‐cell variance is a fundamental characteristic of different biological states 32. Moreover, another study compiled a comprehensive catalog of enhancer histone marks at the single‐cell level, and unveiled that there exists significant de novo establishment of lineage‐specific enhancers during hematopoiesis 25. Similarly, based on single‐cell profiling of histone modifications dynamics in different tissue‐resident macrophages populations, the same group showed that a combination of tissue‐ and lineage‐specific transcription factors form the regulatory networks controlling chromatin specification in tissue‐resident macrophages 26.…”
Section: Single‐cell Profiling Is Key For Studying Pluripotent Statementioning
confidence: 99%
See 3 more Smart Citations